Construção e validação de um protocolo de assistência de enfermagem para pessoas hospitalizadas com traumas ortopédicos - Vieira, Gerlane Ângela da Costa Moreira (2020)
Orthopedic trauma is a sudden traumatic damage to the musculoskeletal and articular system that can lead to functional disabilities and even death, requiring early and effective care. Objective: Build and validate a nursing care protocol for individuals with orthopedic trauma. Methods: This is a methodological study carried out in five stages: survey of empirical indicators and their operational definitions; validation of indicators and their definitions by experts; elaboration of diagnoses, results and interventions based on the International Classification for Nursing Practice; validation of these diagnoses, results and interventions by specialists and structuring of the care protocol, carried out from december 2017 to november 2019. For validation, content validation was used, and for this, the Content Validation Index and the Fleiss Kappa Coefficient were applied. This study was reviewed by the Ethics Committee of the University Hospital Alcides Carneiro and under protocol n°. 3.323.661 and CAAE n°. 10613119.3.0000.5182. Results: It was found that in the first stage, 215 empirical indicators were raised with their operational definitions, of the total 184 correspond to the psychobiological needs, 27 the psychosocial needs and 04 the psycho-spiritual ones. In the second stage, 91 indicators and their operational definitions were validated by 07 specialists in the area of Orthopedic Nursing. In the third one, 98 diagnoses, 84 results and 139 interventions were traced. In the fourth, 33 diagnoses, 07 results and 89 interventions were validated. In the fifth and last one, the assistance protocol was presented. Final Considerations: The construction and validation of this protocol will contribute to the nursing work process, allowing early identification of problems, care planning and assessment of the individual's responses to the care provided.